PENGARUH PENGEMBANGAN HARD SKILL DAN SOFT SKILL TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH INOVASI KERJA PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA KANTOR KELURAHAN DI KOTA SURABAYA - Warmi, Warmi; Wardoyo, Dewie Tri Wijayati; Witjaksono, Andre Dwijanto (ITB AAS Indonesia Surakarta, 2025)
This study aims to examine the effect of developing hard skills, soft skills, and work innovation on the performance of population administration service employees at the Surabaya City Urban Village Office. This research uses a quantitative approach and the data collection technique is done through a survey. The results showed that hard skills have a positive effect on improving employee performance, while soft skills also have a positive impact, although the effect is smaller. Work innovation also has a positive effect on employee performance, but there is no significant influence between soft skills and work innovation. The practical implication of these findings is the importance of developing employee competencies through continuous training and increasing access to the latest technology. In addition, policies that support work innovation and the application of technology in administrative processes must be strengthened to improve the efficiency and quality of population administration services in Surabaya City.